Defluoridation with Locally Produced Thai Bone Char. (18th August 2014) - Mutchimadilok, Yothin; Smittakorn, Sunisa; Mongkolnchai-arunya, Surat; Durnford, Deanna
Abstract : The fluoride sorption ability of a locally available bone char is quantified. Both a synthetic solution and natural groundwater samples from several sites are studied and compared to Indian bone char, which is widely accepted and used successfully in India and elsewhere. The Freundlich and Langmuir sorption isotherms were used to quantify sorption properties. Results show that the Thai bone char is as effective as the Indian bone char for removing fluoride from contaminated water, despite the more rigid physical and social constraints found in rural Thailand. Sorption studies with fluoride-contaminated natural groundwater samples also show that chlorides, nitrates, and sulfates had little effect on the removal of fluoride by the homemade bone char.